Ankara Üniversitesi Astronomi Araştırma Topluluğu, ASART - Altan, İpek (İstanbul Kültür Üniversitesi Yayınları, 2005)
Ankara Üniversitesi Astronomi Araştırma Topluluğu (ASART) 1988 yılında kuruldu. Topluluk çalışmalarına teleskop ve gök atlası yapımı ile başladı ve ayrıca halka açık gözlem şenlikleri düzenledi. Ekim 2002’den itibaren ASART, bir süre ara verdiği aktif çalışmalarını tekrar canlandırdı. Son iki yıldır TÜBİTAK’ın düzenlediği Antalya’daki “Gökyüzü Gözlem Şenliği “ ‘ ne ve Eylül 2004 Erciyes Üniversitesi’nde gerçekleştirilen XIV. Ulusal Astronomi Toplantısı’na topluluk olarak katılım gösterdi. Ankara Üniversitesi Gözlemevi’nde her ayın üçüncü cumartesi gecesi düzenlenen halk günlerinde ve önemli gök olayları için yapılan organizasyonlarda yer aldı. Ayrıca üniversite içi eğitsel çalışmalarda bulunan ASART, seminer ve belgesel film gösterimleri de gerçekleştirmektedir.

Ankara University Amateur Astronomy Clup (ASART) was establised in 1988. The group mainly started working on constructing a telescope and celestial atlas. At the same time the group organized open to public observatory rejoicings. At October 2002 ASART resumed it’s active operations which was suspended for some time. As for last two years ASART as a group has participated in “The Sky Observation Rejoicing” Organized by TÜBİTAK at Antalya and XIV. National Astronomy Meeting organized by The University of Erciyes in 2004. ASART has taken it’s place regularly in important sky events and public days organized by The Ankara University once a month on the third of Saturday. ASART also organizes educational activities within the university and shows seminar film presentations.
Keywords: Amatör Astronomi Topluluğu; Amateur Astronomy Community